Einige litauische Ortssagen, bodenlose Gewässer und Frau Holle (KHM 24, ATU 480)Nekaj litovskih legend o nastanku krajev, vodovje brez dna in Frau Holle (KHM 24, ATU 480) - Gliwa, Bernd (Studia mythologica Slavica, 2005)
The paper discusses Lithuanian legends on sunken animals and objects in lakes and swamps. Moving through a water barrier means passing into the Otherworld, as is seen in tales ATU 480, e.g. „Frau Holle“. Cows resting on the ground of waters are images of the dead in the meadows of the Otherworld. The sinking has been interpretated as a funeral, while the rise to the surface is connected with images of childgiving. It results in the prediction of archeological findings from the 2nd mill. BC in lakes and swamps called Groundless. As corpses may remain conserved in a swamp for a long time this could give interesting results.